PENEGAKAN HUKUM PERWAKAFAN DI INDONESIA - Sofyan Mei Utama (Jurnal Hukum Mimbar Justitia, 2017)
Waqf Institution is a religiously social institution that legally recognizable in Indonesiaunder the guarantees of a Legislation. Waqf is a receptable community life that can bean alternative way in communicating welfare development. Law enforcement on Waqfare now more complete and stronger by the presence of the Indonesian Republic LawNumber 41, 2004 About Waqf and Government Regulation Number 42, 2006Concerning the Implementation of Indonesian Republic Law Number 41, 2004 on Waqf,it was a challenge so that to the law of Waqf can be enforced in Indonesia due to theIslamic shari'ah.